When they overstay their welcome: UN peacekeepers in Africa - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2010)
United Nations (UN) peace operations are once again at a crossroads, partly due to overstretched capacities. Presently, there are indications that UN peace operations face a new and perhaps less expected challenge. Post-conflict peacebuilding faces increasing resistance by the host countries that the UN is seeking to assist. In recent years, the governments of Burundi and the Democratic Republic of the Congo have pushed through the reduction of peacekeeping personnel or forced the wholesale withdrawal of peace operations - despite the concerns of the UN. The case of Chad is similar. The peacekeepers there have a very restricted mandate, but at the request of the Chadian government, the mission will be terminated in late 2010
Keywords: 320